THE INFLUENCE OF DANGDUT MUSIC TO THE BEHAVIOR OF CHILDREN SCHOOL AGE YEAR IN INDONESIA: A LITERATURE REVIEW - Bety Agustina Rahayu; Iman Permana (Journal of Nursing Science Update (JNSU), 2019)
Dangdut music is popular music for some people in Indonesia, especially those from the middle-low socioeconomic group, popular not only for adults but also children, sometimes the lyrics for adults are accompanied by unrestricted visual effects watched by children. The aimed of this study was to the reviewing literature related to the influence of dangdut music on deviations in child behavior. Searching for literature on databases in ProQuest, DOAJ, EBSCO, Pubmed, IPI Google School and Google Education with a range from 2013 to 2017. Using keywords "dangdut music", "behavioral irregularities", "school age children",Â  and 1534 articles were found, in the second phase of the search adding criteria, namely not in autism / mental disorder children and not therapy, obtained 6 journals, in the third stage after reading abstracts and full text, the final results of the 6 journals were obtained. The reviewed journals mentioned that many dangdut song lyrics are meaningful and lead to impoliteness to be heard by school-age children that influence their behavior. Deviations that occur include children mocking friends or parents by behaving imitating the movements of dangdut singers, the development of the language of children who have been influenced by negative vocabulary and improperly spoken by children, children are also more emotional and lacking in religious awareness. In conclusion the influence of dangdut music exposure on behavior deviations in children. With the exposure of dangdut songs to affect children's language style when talking to parents with the pronunciation of vocabulary with negative connotations, children tend to be emotional, attitude when communicating with people who show irreverent ridicule, namely behavior that twists and turns on their bodies. School-age children are childhood times mimicking what he sees, as parents are obliged to play songs that are appropriate, so that children can grow and develop according to their age well.